Interplay between Wheat Cultivars, Biocontrol Pseudomonads, and Soil - Meyer, Joana Beatrice (American Society for Microbiology (ASM), 2010)
There is a significant potential to improve the plant-beneficial effects of root-colonizing pseudomonads by breeding wheat genotypes with a greater capacity to sustain interactions with these bacteria. However, the interaction between pseudomonads and crop plants at the cultivar level, as well as the conditions which favor the accumulation of beneficial microorganisms in the wheat rhizosphere, is largely unknown. Therefore, we characterized the three Swiss winter wheat (Triticum aestivum) cultivars Arina, Zinal, and Cimetta for their ability to accumulate naturally occurring plant-beneficial pseudomonads in the rhizosphere. Cultivar performance was measured also by the ability to select for specific genotypes of 2,4-diacetylphloroglucinol (DAPG) producers in two different soils. Cultivar-specific differences were found; however, these were strongly influenced by the soil type. Denaturing gradient gel electrophoresis (DGGE) analysis of fragments of the DAPG biosynthetic gene phlD amplified from natural Pseudomonas rhizosphere populations revealed that phlD diversity substantially varied between the two soils and that there was a cultivar-specific accumulation of certain phlD genotypes in one soil but not in the other. Furthermore, the three cultivars were tested for their ability to benefit from Pseudomonas inoculants. Interestingly, Arina, which was best protected against Pythium ultimum infection by inoculation with Pseudomonas fluorescens biocontrol strain CHA0, was the cultivar which profited the least from the bacterial inoculant in terms of plant growth promotion in the absence of the pathogen. Knowledge gained of the interactions between wheat cultivars, beneficial pseudomonads, and soil types allows us to optimize cultivar-soil combinations for the promotion of growth through beneficial pseudomonads. Additionally, this information can be implemented by breeders into a new and unique breeding strategy for low-input and organic conditions.